Effect of traditional Chinese exercises on the physical and mental health of stroke patients: a meta-analysis - Shao, Yan; Han, Jing-Yuan; Li, Hai-Long; Ren, Zhu-Ping; Yang, Hui (Frontiers in Neurology, 2024)
The aim of this meta-analysis was to investigate the effects of traditional Chinese exercises on stroke and explore the dose response relationship between the type of exercise and exercise duration with respect to physical and mental health. Methods: We searched PubMed, Web of Science, EBSCO, China National Knowledge Infrastructure (CNKI), Wan Fang Database, and China Science and Technology Journal Database to obtain published randomized controlled trials (RCTs) related to stroke patients and traditional Chinese exercise that meet the evaluation criteria, from the establishment of the database until September 2022. After conducting an evaluation of literature quality, we used RevMan5.4 for data processing. Results: A total of 27 RCTs were included. The results of the meta-analysis revealed that motor function (MD = 4.79, 95% CI: [4.14, 5.43], P < 0.001), balance function (MD = 5.25, 95% CI: [3.93, 6.56], P < 0.001), and mental health (MD = -2.42, 95% CI: [-3.92 to -0.92], P = 0.002) were better in the experimental group than the control group.Traditional Chinese exercise has a beneficial effect on the physical and mental health of stroke patients, wherein, the most significant benefit was with respect to the balance function. The improvement in exercise ability and mental health of stroke patients through traditional Chinese exercise is not correlated with the increase in practice time, however, there are certain duration limitations.